Connecting the Dots : How Research-Based Teaching Shapes Teacher Self-Efficacy and Elevates Professional Development in Education - Jaya, Fitra (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the perception of implementing research-based teaching and teacher self-efficacy in improving professional teaching and learning. This study used a quantitative approach with the survey as a data collection method. 187 teachers were involved in the study spread across three different provincial regions. Data collection was conducted using questionnaires related to teachers' perceptions and self-assessments of research-based teaching, teacher self-efficacy, and professional teaching and learning. The analysis used a two-step approach involving measurement and structural model using structural equation modeling (SEM) analysis. The results showed that research-based teaching has Â an assential role Â in improving professional teaching and learning. In addition, teacher self-efficacy also affects the development of teaching and learning professionals, indicating that teacher confidence in their teaching ability has a significant impact on the quality of student learning. The use of research-based teaching by teachers not only increases the efficacy of their teaching, but also positively impacts the learning experience of students, enriching and expanding the quality of learning.